Fabrication of Fe–Co Magnetostrictive Fiber Reinforced Plastic Composites and Their Sensor Performance Evaluation - Katabira, Kenichi (Materials (Basel), 2018)
The inverse magnetostrictive effect is an effective property for energy harvesting; the material needs to have large magnetostriction and ease of mass production. Fe–Co alloys being magnetostrictive materials have favorable characteristics which are high strength, ductility, and excellent workability, allowing easy fabrication of Fe–Co alloy fibers. In this study, we fabricated magnetostrictive polymer composites, in which Fe–Co fibers were woven into polyester fabric, and discussed their sensor performance. Compression and bending tests were carried out to measure the magnetic flux density change, and the effects of magnetization, bias magnetic field, and the location of the fibers on the performance were discussed. It was shown that magnetic flux density change due to compression and bending is related to the magnetization of the Fe–Co fiber and the bias magnetic field. The magnetic flux density change of Fe–Co fiber reinforced plastics was larger than that of the plastics with Terfenol-D particles.